Improve environmental performance in order to activate sustainable environmental responsibility in business organizations - Case Study of Tebessa Cement Corporation - Hafnaoui, Amel (Social Empowerment Journal, 2019)
Environmental responsibility of business organizations has become an important issue in international community, owing to the expansion of the activities of these organizations at the expense of the environment, as well as their use of environmentally polluting substances in the production process. In this study, the importance of activating sustainable environmental responsibility in business organizations was clarified by focusing on improving their environmental performance, while studying the efforts and endeavors of the Cement Corporation in this field in order to rebalance their relation to environment and activate sustainable environmental responsibility. The study showed that despite the efforts made by the Corporation to protect the environment and improve its environmental performance, which is weak and does not meet the required level, reflecting the weak adoption of the Corporation for its sustainable environmental responsibility, mainly due to the lack of necessary awareness of the human element in the Corporation, Integrate environment into its strategies and processes.